2007
DOI: 10.1117/12.732903
|View full text |Cite
|
Sign up to set email alerts
|

Vertical GaN based light emitting diodes on metal alloy substrate boosts high power LED performance

Abstract: Vertical GaN based Light Emitting Diodes on metal alloy substrate (VLEDMS) were realized and characterized for solid state lighting application. An efficiency of more than 100 lumens/watt from a white LED was achieved. And, an efficiency of more than 80 lumens/watt from a high efficiency and high power green LED was achieved also. The dissipate heat more effectively than conventional and flip-chip LEDs, thanks to the higher thermal conductivity of a copper alloy substrate. This increases their maximum operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In contrast, the vertical LEDs (VLEDs), which enable the wafer bonding of the p-type GaN on substrates such as silicon, silicon carbides, metals, and metal alloys for removing the sapphire substrate, have many advantages of better current injection without current crowding, excellent thermal dissipation, high light extraction, and good reliability [8][9][10][11][12]. For VLEDs, a laser lift-off (LLO) process has been often used to remove the sapphire substrate from the GaN epitaxial layer.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the vertical LEDs (VLEDs), which enable the wafer bonding of the p-type GaN on substrates such as silicon, silicon carbides, metals, and metal alloys for removing the sapphire substrate, have many advantages of better current injection without current crowding, excellent thermal dissipation, high light extraction, and good reliability [8][9][10][11][12]. For VLEDs, a laser lift-off (LLO) process has been often used to remove the sapphire substrate from the GaN epitaxial layer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of Cu substrate not only simplifies the electrode preparation, but also can suppress the current-crowding effect, because the vertical configuration of anode and cathode can yield uniform current spreading [see the inset of Figs. 3(b) and 3(c)] [15,16]. Now, let us briefly discuss the mode and formation mechanism of ZnO lasing.…”
Section: Resultsmentioning
confidence: 99%
“…Though these substrates have an epitaxial relationship with ZnO, their low thermal conductivity and high transparency bring some negative effects, such as poor heat dissipation and light loss in the direction of substrates. These problems can be mitigated by the use of metal substrates [14][15][16][17][18][19]. However, the device fabrication on metal substrates is very difficult because of thermal mismatch and lattice mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lower forward operating voltage of VLEDs can be obtained, leading to a reduced thermal load. Doan et al found that the forward I–V curves of GaN-based VLEDs was steeper compared with the lateral structure, indicating a reduced series resistance [36]. A forward voltage of vertical LEDs around 4.5 V at 200 mA compared to 5.8 V for lateral LED on sapphire was reported by Cao et al [37].…”
Section: Introductionmentioning
confidence: 95%